Real-Time Intelligent IoT-Based Drum Brake Temperature Monitoring System - Maulana Yusuf Alkahfi; Raka Pratindy; M. Iman Nur Hakim; Nanang Okta Widiandaru (Journal of Vocational, Informatics and Computer Education, 2026)
Purpose – This study addresses brake system failures in heavy vehicles caused by excessive thermal buildup in drum brakes. Existing monitoring systems rely on single-parameter sensing and lack early warning capabilities, thereby increasing the risk of brake fade and accidents. This study aims to develop a real-time monitoring system to improve safety. Methods: A Research and Development (R&D) approach was applied, including system design, implementation, and testing. The proposed system integrates a Raspberry Pi 4 Model B, Type K thermocouple, ESP32-C3 Super Mini, and GPS NEO-6M module. The data were transmitted via the Thingspeak IoT platform and displayed on a 7-inch TFT touchscreen. Experimental validation includes thermocouple calibration, GPS speed testing, and IoT latency measurement Findings – The thermocouple achieved a mean absolute error of 7.2°C and a percentage error of 3.4% (96.6% accuracy). The GPS speed measurement showed a 2.6% error (97.4% accuracy). IoT latency ranged from 1.2–2.0 s, with 100% data transmission success. The system reliably triggered alerts when the temperature exceeded 360°C, confirming effective real-time monitoring. Research implications: Limitations include dependence on Internet connectivity, environmental effects on sensors, and scalability challenges. Future work should focus on improving robustness and integrating predictive features. Originality – The developed system demonstrates reliable performance at the prototype level. However, the validation was conducted under controlled conditions using a single sensor and without vehicle load. Therefore, further validation under varying load conditions, road gradients, and multipoint brake measurements is required before practical large-scale deployment.